Growth and Yield of White Bok Choy Plants (Brassica rapa subsp. chinensis) across Various Media Compositions in an Urban Environment - Ade Sumiahadi; Tania Amelya Putri (CIB Nusantara, 2025)
White bok choy is a vegetable from the Brassicaceae family that holds high economic value and is highly sought after by consumers. However, its cultivation is often constrained by the selection of appropriate growing media, especially in limited urban spaces. This study aimed to determine the effect of different growing media compositions on the growth and yield of white bok choy plants. The research was conducted from January to February 2025 in the backyard area of a house located in Ciputat District, South Tangerang City. A Randomized Complete Block Design (RCBD) was used with six treatment levels: soil (control); organic growing media; soil + rice husk charcoal (1:1); soil + organic growing media (1:1); organic growing media + rice husk charcoal (1:1); and soil + rice husk charcoal + organic growing media (1:1:1), each replicated four times. The results showed that the composition of the growing medium had no significant effect on any of the observed variables. Soil alone as the growing medium produced comparable results to other growing media and can be recommended as an efficient growing medium for white bok choy cultivation.